Study of metabolic flux distribution in rice (Oryza sativa) cultures for starch production - Abdul Nuri, Nur Aqila Syafiqa; Mohamad Puad, Noor Illi; Abduh, Muhammad Yusuf; Azmi, Azlin Suhaida (2021)
The demand for starch-rich crops remains high due to its wide applications. One of them is rice (Oryza sativa) which is the second most widely grown cereal crop. The large-scale production of rice facing challenges such as unstable productivity, climate changes and excessive use of agrochemicals. Plant cell culture technology is proposed to increase rice yield and producing drought-resistance variety of rice for sustaining its demand. However, the amount of starch in rice cultures is expected to be smaller compared to the planted ones. This is because plant tissue culture only involves the growth of cells, not the whole plant in which certain enzymes may not exist. The main aim of this study is to apply Flux Balance Analysis (FBA) for optimizing starch production in rice cultures. In this study, the stoichiometric metabolic model for starch production in rice has been reconstructed based on the published articles. Upon the reconstruction, the model consists of 160 reactions and 148 metabolites which represents the main carbon metabolism of rice towards starch production. The model was then formulated in GAMS v31.1.0 and the objective function was set to the maximization of starch. The selected constraints (sugar uptake rates and cell growth rates) from previous studies were utilized. The simulated starch production rate values were achieved at the highest glucose uptake rates with the value of 0.0544 mmol/g CDW.h and 0.0067 mmol/g CDW.h for cell suspension and callus culture, respectively. The internal metabolic flux distributions demonstrated that the incoming carbon fluxes were directed towards the glycolysis pathway, TCA cycle, PPP cycle and finally starch biosynthesis reactions. The results of this study serve as a starting point to further understanding the starch production mechanism in plants which are known to be complex and thus, the strategies for improving starch production can be established.